Factors that contribute to obesity problem among UTHM catering student - Ahmad, Nor Aziah; Ahmad Nazri, Naziatul Syarmila (Penerbit UTHM, 2021)
Negative perception by the society and the hospitality industry toward the disabled people is very high and it has to be changed and this parties should be given opportunity to work in this industry. Rosli, et al (2011) states the acceptance in the small and medium industries towards the disabled is at moderate level. However, in 2005, Ministry of Higher Education Malaysia (KPTM) has initiated Polytechnic Ibrahim Sultan, Johor Bahru conduct a pioneer program to produce graduates with disabilities (OKU) with hearing impairments for a career in the hotel industry. Related to the situation, some lecturers were sent to attend sign language courses for the preparation for the program, some facilities were updated to fit their needs. To this present Polytechnic Ibrahim Sultan, Johor Bahru has produced hundreds of OKU graduates. It is hope that the graduates produced from this program could reduce the number of foreign worker working in the industry. Dependence on foreign workers should be reduced because there are almost 2.6 million people with special needs in Malaysia. Some of them have been able to pursue their studies to diploma and Bachelor degrees. Through the development of education they are participated in, it is hoped that they will also contribute to the country's economy. The Government of Malaysia is in the effort to transform employers' perceptions towards this group to be more positive. Thus, several initiatives or benefits had been made by the Government of Malaysia to attract more government link companies (GLC) and private firms to hire people from this group. However there are also some challenges and obstacles faced by the industry in accepting these graduates at their company. Taheing (1996) states that in its study it has been able to identify problems that limit the employment of disabled persons including physiological factors, disability due to defects, occupational types, gender factors, workplace environment, personality, illness and other disabilities. This is a challenge and obstacle faced by the employer in hiring the disabled graduates in their industry. Therefore, the industry is highly concerned with the selection of highly capable employees in helping to increase profits to the company.